Anti-inflammatory effects of miR-21 in the macrophage response to peritonitis. Issue 2 (17th September 2015) - Barnett, Rebecca Elise; Conklin, Daniel J; Ryan, Lindsey; Keskey, Robert C; Ramjee, Vikram; Sepulveda, Ernesto A; Srivastava, Sanjay; Bhatnagar, Aruni; Cheadle, William G
Abstract : MiRNA-21 is beneficial in survival following induction of peritonitis with LPS by limiting the pro-inflammatory phase of the innate response. Abstract: We investigated the role of microRNA-21 in the macrophage response to peritonitis; microRNA-21 expression increases in peritoneal macrophages after lipopolysaccharide stimulation but is delayed until 48 hours after cecal ligation and puncture. MicroRNA-21–null mice and bone marrow–derived cell lines were exposed to cecal ligation and puncture or lipopolysaccharide, and survival, microRNA-21 levels, target messenger RNAs and proteins, and cytokines were assayed. Macrophages were also transfected with microRNA-21 mimics and antagomirs, and similar endpoints were measured. Survival in microRNA-21–null mice was significantly decreased after lipopolysaccharide-induced peritonitis but unchanged after cecal ligation and puncture compared with similarly treated wild-type mice. MicroRNA-21 expression, tumor necrosis factor-α, interleukin 6, and programmed cell death protein 4 levels were increased after lipopolysaccharide addition in peritoneal cells. Pelino1 and sprouty (SPRY) messenger RNAs were similarly increased early, whereas programmed cell death protein 4 messenger RNA was decreased after lipopolysaccharide, and all microR-21 target messenger RNAs were subsequently decreased by 24 hours after lipopolysaccharide. Transfection with mimics and antagomirs led to appropriate responses in microRNA-21 and tumor necrosis factor-α. Knockdown of microRNA-21 in bone marrow–derived cells showed increased tumor necrosis factor-α and decreased interleukin 10 in response to lipopolysaccharide. Target proteins were unaffected by knockdown as was extracellular signal-regulated kinase; however, the nuclear factor κB p65 subunit was increased after lipopolysaccharide in the microRNA-21 knockout cells. In contrast, there was little change in these parameters after cecal ligation and puncture induction between null and wild-type mice. MicroRNA-21 is beneficial to survival in mice following lipopolysaccharide peritonitis. Overexpression of microRNA-21 decreased tumor necrosis factor-α secretion, whereas suppression of microRNA-21 expression increased tumor necrosis factor-α and interleukin 6, and decreased interleukin 10 levels after lipopolysaccharide. Protein targets of microRNA-21 were not different following suppression of microRNA-21. Nuclear factor κB was increased by suppression of microRNA-21. These findings demonstrate microRNA-21 is beneficial in modulating the macrophage response to lipopolysaccharide peritonitis and an improved understanding of the anti-inflammatory effects of microRNA-21 may result in novel, targeted therapy against peritonitis and sepsis.